PEMAHAMAN HADIS TENTANG OPTIMISME - Hatifah, Siti; Nirwana, Dzikri (Jurnal Studia Insania, 2014)
Understanding of hadith (fiqh al-hadith) is a process of understanding that comes from the hadith of Prophet Muhammad and studies which explores and comprehends the teachings contained in the hadith of the Prophet to be applied. One of the faithful? characteristics is to have an optimistic attitude. Without having an optimistic attitude, someone will destroy himself. For example, he is easily stress, sad, disappointed, depression, and even suicide. Therefore, an optimistic attitude is very important thing, because optimism is the belief of everything in terms of good and fun, it always has positive thinking and has high expectations.